SfC Home > Physics > Wave Motion >

# Doppler Effect Frequency Equations

by Ron Kurtus

The Doppler Effect causes the observed frequency of a waveform to change according to the velocity of the source and/or observer. The Doppler Effect frequency equations can derived by starting with the general wavelength equation.

After the general frequency equation is determined, you can find the frequency equations for a moving source and stationary observer and moving observer with a stationary source.

In the equations, it is assumed that the motion is constant and in the x-direction.

Questions you may have include:

• What is the general frequency equation?
• What are the equations for a moving source and stationary observer?
• What are the equations for a moving observer and stationary source?

This lesson will answer those questions. Useful tool: Units Conversion

## General frequency equation

In order to establish the general Doppler Effect frequency equation—where both the source and observer are moving—you start with the previously derived general wavelength equation and put it in terms of frequency. Start with:

λO = λS(c − vS)/(c − vO)

where

• λO is the observed wavelength
• λS is the constant wavelength from the source
• c is the constant velocity of the wavefront in the x-direction
• vS is the constant velocity of the source in the x-direction
• vO is the constant velocity of the observer in the x-direction

Substitute λO = c/fO and λS= c/fS in the equation to get:

c/fO= (c/fS)[(c − vS)/(c − vO)]

c/fO= c(c − vS)/fS(c − vO)

where

• fO is the constant observed frequency
• fS is the constant source frequency

Divide both sides by c and reciprocate the equation. This results in the general frequency equation:

fO = fS(c − vO)/(c − vS)

The equation is often written in the convenient format:

fO/(c − vO) = fS/(c − vS)

### Change in frequency

The change in frequency or Doppler frequency shift is:

Δf = fS − fO

Substitute in fO = fS(c − vO)/(c − vS):

Δf = fS − fS(c − vO)/(c − vS)

Combine terms:

Δf = [fS(c − vS) − fS(c − vO)]/(c − vS)

Δf = (fSc − fSvS− fSc + fSvO)/(c − vS)

Thus:

Δf = fS(vO vS)/(c − vS)

## Moving source and stationary observer

When the source is moving in the x-direction but the observer is stationary, you can take the general frequency equation, set vO = 0, and solve for fO. Source is moving toward stationary observer

The general frequency equation is:

fO = fS(c − vO)/(c − vS)

Set vO = 0 and solve for fO:

fO = fSc/(c − vS)

The equation is often seen in the form:

fO = fS/(1 − vS/c)

### Change in frequency

The change in frequency or Doppler frequency shift is:

Δf = fS − fO

Note that when the source is moving toward the observer, fS > fO and Δf is negative.

Substitute for fO:

Δf = fS fSc/(c − vS)

Factor out fS:

Δf = fS[1 − c/(c − vS)]

Simplify:

Δf = fS[(c − vS)/(c − vS) − c/(c − vS)]

Δf = fS(c − vS c)/(c − vS)

Δf = fS(− vS)/(c − vS)

Thus:

Δf = −fS vS/(c − vS)

## Moving observer and stationary source

When the observer is moving in the x-direction but the source is stationary, you can take the general frequency equation, set vS = 0, and solve for fO. Observer moving away from oncoming waves

Set vS = 0 in the general frequency equation:

fO = fS(c − vO)/(c − vS)

Thus:

fO = fS(c − vO)/c

or

fO = fS(1 − vO/c)

Note: Stating the direction convention is very important. Often the equation will be written with the observer moving toward the source, resulting in the equation: fO = fS(1 + vO/c). Make sure you know the convention used.

### Change in frequency

The change in frequency is:

Δf = fS − fO

Substitute for fO:

Δf = fS − fS(c − vO)/c

Simplify:

Δf = cfS/c − fS(c − vO)/c

Δf = (cfS − cfS + vOfS)/c

Thus:

Δf = vOfS/c

Note: According to our direction convention, vO becomes −vO when the observer is moving toward the source.

## Summary

The Doppler Effect frequency equations can be readily determined from the derived general wavelength equation. The resulting general Doppler Effect frequency equation is:

fO/(c − vO) = fS/(c − vS)

From the general equation, the equation for the case when the observer is stationary can be found be setting vO = 0.

fO = fSc/(c − vS)

Δf = −fS vS/(c − vS)

Likewise, the equation when the source is stationary can be found be setting vS = 0.

fO = fS(c − vO)/c

Δf = vOfS/c

Sometimes you need to improvise

## Resources and references

Ron Kurtus' Credentials

### Websites

Wave Motion Resources

### Books

(Notice: The School for Champions may earn commissions from book purchases)

Top-rated books on the Doppler Effect ## Students and researchers

www.school-for-champions.com/science/
waves_doppler_effect_frequency_derivations.htm

## Where are you now?

School for Champions

Physics topics

## Also see

### Let's make the world a better place

Be the best that you can be.

Use your knowledge and skills to help others succeed.

Don't be wasteful; protect our environment.

### Live Your Life as a Champion:

Seek knowledge and gain skills

Do excellent work

Be valuable to others

Have utmost character

#### Be a Champion!

The School for Champions helps you become the type of person who can be called a Champion.